1990
DOI: 10.1002/j.1460-2075.1990.tb07397.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the modulation of ada promoter activity by upstream elements.

Abstract: We have determined the kinetics of initiation of transcription of the wild‐type ada promoter by abortive initiation assays. In the absence of activation, it is a weak promoter, with an association constant KB and an isomerization rate constant k2 comparable to those obtained under the same conditions for other positively regulated promoters (0.36 x 10(7) M‐1 and 1.7 x 10(‐2) s‐1, respectively, at 37 degrees C and 50 mM NaCl, on a supercoiled template). As already observed for other promoters, these constants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…DNA curvature has been observed or predicted from sequence data in the upstream regions of a number of promoters, where it is believed to play an important role in increasing transcription rates. Sequences upstream of the -35 regions of such promoters generally contain phased tracts of A, or Tn (2,4,27,36,47), which are known to favor intrinsic DNA bending (29). In addition, induced DNA bending is thought to be a significant factor in the mechanism of a number of transcriptional activators (46,59), of which the most extensively studied is the E. coli catabolite gene activator protein (CAP) (reviewed in reference 28).…”
Section: Discussionmentioning
confidence: 99%
“…DNA curvature has been observed or predicted from sequence data in the upstream regions of a number of promoters, where it is believed to play an important role in increasing transcription rates. Sequences upstream of the -35 regions of such promoters generally contain phased tracts of A, or Tn (2,4,27,36,47), which are known to favor intrinsic DNA bending (29). In addition, induced DNA bending is thought to be a significant factor in the mechanism of a number of transcriptional activators (46,59), of which the most extensively studied is the E. coli catabolite gene activator protein (CAP) (reviewed in reference 28).…”
Section: Discussionmentioning
confidence: 99%
“…UP elements, when present, are integral components of promoters, because they interact with the carboxy terminal domain of the RNAP ␣-subunit (12). In vitro studies showed that the E. coli RNAP ( 70 ) holoenzyme alone is sufficient for transcriptional activity from several such promoters (12,14,15).…”
mentioning
confidence: 99%
“…These are the -35 region, having the consensus sequence TTGACA, a spacer of 17_+2 base pairs, and the -10 region, or Pribnow box, which has the consensus sequence TATAAT (Harley and Reynolds 1987). In some promoters, there is a fourth AT-rich stretch downstream of the --35 region which may be involved in bending the promoter around RNA polymerase (Bertrand-Burggraff et al 1990), or other sites which are recognised by transcriptional activators such as the catabolite activator protein (de Crombrugghe et al 1984).…”
Section: Introductionmentioning
confidence: 98%